Determinants of target capital structure: evidence on South East Asia countries - Mat Nor, Fauzias; Haron, Razali; Ibrahim, Khairunisah; Ibrahim , Izani; Alias, Norazlan (World Business Institute, Australia, 2011)
The purpose of this study is to identify the existence of target capital structure and to examine the determinants of target capital structure for selected countries in the South East Asia region using the dynamic framework. We analyse the impact of country specific determinants along with firm specific determinants on the corporate structure decisions within the firms in the countries understudy. We find that the importance of firm specific determinants varies across countries for firms in the selected countries in the region. The introduction of country specific variables such as the level of stock market development, bond market development, economic growth, interest rates and country governance support and enhance these findings. The importance of country determinants also varies across countries understudy despite sharing some similarities. Our findings contribute to the existing literature by documenting strong evidence that firms in the selected countries do pursue target capital structure. Simultaneously, we also witness cases of inconsistencies regarding the impact of factors on capital structure in the countries understudy. To wrap up, we conclude that the capital structure decision is not only the product of the firm’s own characteristics but also the result of institutional environment and corporate governance in which the firm operates.